Peningkatan Literasi Remaja Karang Taruna terhadap Risiko Intrusi Air Laut pada Air Sumur di Kota Semarang melalui Edukasi Partisipatif - Putra, Muhammad Abrian Surya (Jurnal Pengabdian KOLABORATIF, 2026)
Seawater intrusion is one of the major environmental issues in the coastal area of Semarang City, affecting the quality of groundwater used by local communities, particularly from shallow wells. Low environmental literacy, especially among adolescents, may hinder early detection and risk mitigation efforts related to this problem. From a civil and environmental engineering perspective, limited public understanding of groundwater dynamics and coastal hydrogeology can exacerbate the overexploitation of aquifers and accelerate saline water intrusion. This community engagement program aimed to enhance the environmental literacy of youth community members regarding the risks of seawater intrusion through participatory education. The method employed an interactive training approach, including material presentations on coastal hydrogeology, groundwater management, and saline intrusion mechanisms, followed by group discussions and evaluation through pre-test and post-test assessments involving 15 participants. The results demonstrated an improvement in participants’ understanding by 31 points, equivalent to a 57% increase compared to the baseline condition. After the program, participants were able to explain more systematically the causes of seawater intrusion, such as excessive groundwater extraction, land subsidence, and reduced recharge areas, its impact on well water quality, and the importance of sustainable groundwater management practices. During the discussion sessions, several participants began relating the material to local environmental conditions, including the phenomenon of increased salinity in well water during the dry season. These findings indicate that participatory educational approaches are effective in strengthening environmental literacy within a civil and environmental context. The program concludes that participatory education can serve as a relevant strategy to empower youth as agents of environmental awareness, supporting sustainable groundwater management and coastal resilience efforts.